Pengembangan Media Pembelajaran Mobile Learning Berbasis Android pada Materi Sifat Koligatif Larutan - Septina Restu; Suhartono; Ucu (Jurnal Riset Pendidikan Kimia (JRPK), 2017)
This study aims to develop a mobile learning media for the smartphone on the material of the colligative nature of the solution. This research uses the research approach of developing the model of Borg & Gall that has been adapted. The research stages consist of needs analysis, media development, and media trials. The result of requirement analysis shows that 91,7% of students felt the need for the development of mobile learning media on the material of the colligative nature of the solution. Media developed this form of particular applications for android with size 49.49 MB. Experimental results by media experts obtained a feasibility percentage of 87.2%. Test results obtained by the material expert received a portion of eligibility of 88%. Trial results to the chemistry teacher achieved by 94%. Trial results to small-scale students were reached at 79%. Trial results to large-scale students were reached at 80%. From the whole test, it can be concluded that Android Based Learning Learning Media On Material Colligative Material The solution has been by the needs of students and teachers with good interpretation results. Keywords: Learning Media of Chemistry, Mobile Learning, Android, Colligative, Properties of Solution